Exploring the relationship between role ambiguity and job performance among employees of the service sector SMES in Malaysia / Sethela June and Rosli Mahmood - June, Sethela; Mahmood, Rosli (Universiti Teknologi MARA, Perlis, 2011)
Small and medium size enterprises (SMEs) play a crucial role in the economic development of Malaysia. The service sector forms the largest sector of the SMEs establishments. Employees of the service sector SMEs have often been associated with low level of job performance and past research have shown that there are many factors that can contribute to employee poor performance. One of the factors that often been associated with poor job performance is when employees experiences role ambiguity. Thus the main aim of this conceptual paper is to present a conceptual understanding on the relationship that exists between role ambiguity and job performance.